Reform of The Law on The Division of Joint Property Divorce - Habib Rasyidi Daulay; Idzam Fautanu; Sirajuddin Sailellah (CV. Publikasi Indonesia, 2024)
The purpose of this study is to find out reform of the law on the division of joint property divorce. 50-fifty provisions regarding the sharing of joint assets are often applied rigidly in accordance with the provisions of Article 97 of the KHI. The resulting output does not provide a sense of justice to the parties. This research is normative law with a substantive analysis approach to the provisions of Article 97 of the KHI. The results showed that the sharing of joint assets was regulating (regelen) not coercive (dwingon). In certain cases, this provision can be deviated by contextualizing it through the maqashid sharia approach to the substance of the case. The amount of the contribution of either party to the acquisition of joint assets and commitment to the sacred promise of marriage is a modifying element ('illat) in the case of sharing of joint assets. Maqashid shari'ah as an instrument in law making (istinbath) plays a very large role in this case, especially if the case presented is closely related to distributive justice where the elements of benefit and the purpose of the law are the main benchmark in seeking justice. Contextual reasoning and a substantive approach to the purpose of article 97 KHI by prioritizing psychological and contributive aspects to the case of division of joint property will make the article flexible. In the event that the role of one party is greater in the acquisition of joint property and there is an attitude of inconsistency of one party towards marital commitment, it becomes a ratio legis of reduced share of joint property of the former husband and wife.